iWalk:intelligent walking stick for visually impaired subjects - Olanrewaju, Rashidah Funke; Mohd Radzi, Muhammad Luqman Azzaki; Rehab, Mariam (10.1109/ICSIMA.2017.8312000, 2018)
Visually impaired people find great difficulty in moving around freely without a human guide, especially in a new terrain. iWalk is an intelligent walking stick specially designed for visually disabled individuals to improve and ease navigation. iWalk uses ultrasonic and water sensors to detect obstacles and water ahead. The water sensor integrated therein activates a distinct buzzer if it detects water. The system comes with a wireless RF remote control that uniquely sounds buzzier when pressed, that helps in locating the stick in case it gets misplaced. The efficiency of the proposed solution has been adequately tested on a dataset composed of randomized locations with obstacles and water. The proposed algorithm achieves an overall efficiency of 90% detection rate for water and ultrasonic sensor and 85.75% for the RF wireless remote control.